Unravelling the role of HAS2, GREM1, and PTGS2 gene expression in cumulus cells: implications for human oocyte development competency - a systematic review and integrated bioinformatic analysis - Faizal, Ahmad Mohd; Elias, Marjanu Hikmah; Jin, Norazilah Mat; Abu, Muhammad Azrai; Syafruddin, Saiful Effendi; Zainuddin, Ani Amelia; Suzuki, Nao; Karim, Abdul Kadir Abdul (Frontiers in Endocrinology, 2024)
The leading indicator for successful outcomes in in-vitro fertilization (IVF) is the quality of gametes in oocytes and sperm. Thus, advanced research aims to highlight the parameter in assessing these qualities -DNA fragmentation in sperm and oocyte development capacity (ODC) via evaluation of microenvironments involving its maturation process. Regarding oocytes, most evidence reveals the role of cumulus cells as non-invasive methods in assessing their development competency, mainly via gene expression evaluation. Our review aims to consolidate the evidence of GDF-9 derivatives, the HAS2, GREM1, and PTGS2 gene expression in cumulus cells used as ODC markers in relevant publications and tailored to current IVF outcomes. In addition to that, we also added the bioinformatic analysis in our review to strengthen the evidence aiming for a better understanding of the pathways and cluster of the genes of interest -HAS2, GREM1, and PTGS2 in cumulus cell level. Otherwise, the current non-invasive method can be used in exploring various causes of infertility that may affect these gene expressions at the cumulus cell level. Nevertheless, this method can also be used in assessing the ODC in various cohorts of women or as an improvement of markers following targeted tools or procedures by evaluating the advancement of these gene expressions following the targeted intervention.